Performance analysis and synthesis for discrete-time stochastic systems with network-enhanced complexities - Ding, Derui; Wang, Zidong, 1966-; Wei, Guoliang (Boca Raton, FL : CRC Press/Taylor & Francis Group, 2019)
The book addresses the system performance with a focus on the network-enhanced complexities and developing the engineering-oriented design framework of controllers and filters with potential applications in system sciences, control engineering and signal processing areas. Therefore, it provides a unified treatment on the analysis and synthesis for discrete-time stochastic systems with guarantee of certain performances against network-enhanced complexities with applications in sensor networks and mobile robotics. Such a result will be of great importance in the development of novel control and filtering theories including industrial impact. Key Features: Provides original methodologies and emerging concepts to deal with latest issues in the control and filtering with an emphasis on a variety of network-enhanced complexities; Gives results of stochastic control and filtering distributed control and filtering, and security control of complex networked systems; Captures the essence of performance analysis and synthesis for stochastic control and filtering; Concepts and performance indexes proposed reflect the requirements of engineering practice; Methodologies developed in this book include backward recursive Riccati difference equation approach and the discrete-time version of input-to-state stability in probability.
OCLC-licensed vendor bibliographic record.
Keywords: Automatic control -- Mathematics; Stochastic processes; Discrete-time systems; TECHNOLOGY & ENGINEERING / Engineering (General); MATHEMATICS / Differential Equations; TECHNOLOGY / Electricity